2014
DOI: 10.1159/000362556
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Leflunomide and Benazepril in Streptozotocin-Induced Diabetic Nephropathy

Abstract: Background: Leflunomide (LEF) and benazepril have renoprotective effects on diabetic nephropathy (DN) through their anti-inflammatory and anti-fibrotic activities. This study investigated whether combined treatment using LEF and benazepril affords superior protection compared with the respective monotherapies. Methods: Diabetes was induced with streptozotocin (STZ, 65 mg/kg) by intraperitoneal injection in male Wistar rats. Two weeks after STZ injection, diabetic rats were treated daily for 12 weeks with LEF (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…It has been confirmed that angiotensin converting enzyme inhibitor (ACEI) drugs can lower blood pressure and reduce significant proteinuria, protecting the kidneys and delaying the progression of kidney disease (32). Clinically, benazepril, a type of ACEI, is important in ameliorating diabetic kidney damage (33). In the present study, benazepril treatment was used as a positive control, and the results showed that tacrolimus and benazepril significantly reduced the levels of urinary protein, Scr and BUN in groups F and L, compared with those in group DN (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that angiotensin converting enzyme inhibitor (ACEI) drugs can lower blood pressure and reduce significant proteinuria, protecting the kidneys and delaying the progression of kidney disease (32). Clinically, benazepril, a type of ACEI, is important in ameliorating diabetic kidney damage (33). In the present study, benazepril treatment was used as a positive control, and the results showed that tacrolimus and benazepril significantly reduced the levels of urinary protein, Scr and BUN in groups F and L, compared with those in group DN (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the expression of TLR2 and TLR4 was enhanced in STZ-induced rat models of diabetes mellitus 164,165 and global deletion of Tlr4 in mice resulted in decreased renal inflammation and fibrosis associated with the reduction in the expression of MCP-1 147 .…”
Section: [H2] Influence Of Chemokinesmentioning
confidence: 99%
“…As a result, chronic TAC nephropathy involves both renal dysfunction and proteinuria [3]. It is well known that TGF-β1 plays a pivotal role in renal scarring in a wide range of kidney diseases probably by its action on ECM synthesis and degradation [25-27]. It has been confirmed by in vivo and in vitro studies that TAC induces TGF-β1 expression either directly or indirectly.…”
Section: Discussionmentioning
confidence: 99%